A biogeographical regionalization of coastal Mediterranean fishes. (6th April 2015) - Hattab, Tarek; Albouy, Camille; Ben Rais Lasram, Frida; Le Loc'h, François; Guilhaumon, François; Leprieur, Fabien
Abstract Aim To delineate the biogeographical regions of the continental shelf of the Mediterranean Sea based on the spatial distributions of coastal marine fishes and their evolutionary relationships, with a view to furthering our capacity to answer basic and applied biogeographical, ecological and evolutionary questions. Location Mediterranean Sea. Methods We used a dataset summarizing the occurrences of 203 coastal Mediterranean fishes (0.1° resolution grid system) and a molecular phylogenetic tree to quantify both compositional and phylogenetic dissimilarity (or beta diversity) between cells. We then applied multivariate analyses to delineate biogeographical regions and to evaluate how they related to broad‐scale environmental gradients. We also assessed the differences between the biogeographical regions identified using phylogenetic beta diversity versus those obtained using compositional beta diversity. Results The bioregionalization schemes based on phylogenetic and compositional beta diversity identified broadly similar regions, each consisting of six distinct pools of coastal fishes. Clear separations between northern and southern regions were observed, as well as a disjunct between inshore and offshore areas. These beta diversity patterns were mainly related to a north–south gradient in sea‐surface temperature and bathymetric constraints. Main conclusions Incorporating phylogenetic information into the measurement of beta diversity did not offer further insights to the bioregionalization scheme based solely on compositional beta diversity. This suggests that evolutionary and historical processes played only a minor role in shaping the contemporary patterns of beta diversity in the Mediterranean coastal fish fauna. However, our results support the view that contemporary environmental conditions play a major role in determining the distribution of these species.